2005
DOI: 10.1038/nature03625
|View full text |Cite
|
Sign up to set email alerts
|

Expanded T cells from pancreatic lymph nodes of type 1 diabetic subjects recognize an insulin epitope

Abstract: In autoimmune type 1 diabetes, pathogenic T lymphocytes are associated with the specific destruction of insulin-producing beta-islet cells. Identification of the autoantigens involved in triggering this process is a central question. Here we examined T cells from pancreatic draining lymph nodes, the site of islet-cell-specific self-antigen presentation. We cloned single T cells in a non-biased manner from pancreatic draining lymph nodes of subjects with type 1 diabetes and from non-diabetic controls. A high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
340
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(359 citation statements)
references
References 28 publications
14
340
0
5
Order By: Relevance
“…Furthermore, although a lack of a systemic response to insulin peptides in T1D patients, expanded T cells recognising an insulin epitope have been observed in draining pancreatic lymph nodes (Kent 2005). Together with the findings presented in this thesis, these observations support the thought that T cells present in the diseased organ more accurately reflect the cell population relevant for the disease process.…”
Section: The Relevance Of Csf Lymphocytes In the Studies Of Ms And Spssupporting
confidence: 77%
“…Furthermore, although a lack of a systemic response to insulin peptides in T1D patients, expanded T cells recognising an insulin epitope have been observed in draining pancreatic lymph nodes (Kent 2005). Together with the findings presented in this thesis, these observations support the thought that T cells present in the diseased organ more accurately reflect the cell population relevant for the disease process.…”
Section: The Relevance Of Csf Lymphocytes In the Studies Of Ms And Spssupporting
confidence: 77%
“…Both proinflammatory and regulatory insulin-reactive T cells have been identified in T1D patients and healthy control subjects who were HLA class II restricted. [16][17][18][19][20] However, few detailed data exist on insulin-specific T-cell clones, which are derived from new-onset T1D patients, and epitopes of insulin-reactive T cells and their cytokine profiles have not been investigated in the context of susceptibility and protective DQ alleles. 21,22 To gain a better understanding of the disease process, we hypothesize that DQ molecules composed of a and b chains from both the DQ2 and DQ8 haplotypes express unique b-cell epitopes, whereas DQ6 binding may interfere with peptide binding to DQ8.…”
Section: Introductionmentioning
confidence: 99%
“…This is a difficult issue, since it is difficult to obtain pancreata from recently-diagnosed T1D patients, but when these tissues have been available their analyses indicated that similar autoreactive T cell specificities can be identified. For example, for pre-proinsulin, DR4-restricted CD4 + T cell clones specific for the A-chain 1-15 epitope were the most dominant amongst the clones isolated from pancreatic lymph nodes (Kent et al 2005); these were also detected in the peripheral blood of children with recently-diagnosed T1D (Marttila et al 2008).…”
Section: T Lymphocytes In T1d: Targets and Peripheral Detectionmentioning
confidence: 99%